BUDGET ANALYSIS AS ONE OF THE PLANNING TOOLS AND PRODUCTION CONTROL - Railis, Hendra (International Journal of Multidisciplinary Research and Literature, 2022)
A developing company must have a goal so that activities within the company can achieve these goals. It is necessary to have a plan accompanied by effective control. One tool that can meet the planning and control needs is a budget because the budget is formal and systematic rather than the exercise of management responsibilities in planning, coordination, and oversight. This study aims to determine the role of the budget as a means of planning and controlling production and to find out the application of the budget to the "Bahana Donut" home industry in City X. The type of approach in this research is the descriptive research method approach in case studies. The data analysis model in this study is to collect sales volume in 2018-2020. From this analysis, the results obtained that: (1) the home industry "Bahana Donut" in City X has an advantage in producing donuts every year because this donut entrepreneur has not made a budget for production activities, to overcome this problem, the home industry "Bahana Donut" "City X requires the role of the budget as a means of planning and controlling production. (2) The production budget for donuts in 2021 is 39670 with a budget for wheat raw materials of 13223.64 Kg and a budget for purchasing wheat raw materials of Rp. 92,894,760, the budget for raw materials for sugar is 22003.94 Kg, and the budget for purchasing raw materials for sugar is Rp. 13,230,840, the budget for raw materials for eggs is 1101.97 Kg. The budget for purchasing raw materials for eggs is Rp. 13,227,960, the budget for raw materials for butter is 2203.94 Kg, and budget for purchasing raw materials for butter is Rp. 22,401,800, the budget for raw materials for oil is 3305.91 Kg, and the budget for purchasing raw materials for oil is Rp. 39,703,320